N^2(n - 1) + 3(n - 1)
(n^2 + 3)(n - 1)
the answer is c
<span>Given:
f(0) = 2</span>
So first of all, we let x = 2012, y = 0:
<span>
Then, F(2012) = 2012 + f(0)
Since f(0) = 2, then f(2012) = 2012 + 2 = 2014.
To add, </span>the process that relates an input to an output is called a
function.
<span>There are always three main parts of a
function, namely:
</span>Input
The Relationship
The Output
The classic way of writing a function is
"f(x) = ... ".
What goes into the function
is put inside parentheses () after the name of the function: So, f(x) shows us the
function is called "f", and "x" goes in.
What a function does with the input can be usually seen as:
<span>f(x) = x2</span><span> reveals to us that function "f" takes "x<span>" and squares
it.</span></span>
No 5/8 is not greater then 2/3, 5/8 is just 1/24 smaller then 2/3.
(a^3-2a^2)-(3a^2-4a^3)
(a^3-2a^2)-3a^2+4a^3
5a^3-5a^2